INOVASI PAKAN ALTERNATIF ITIK PETELUR MELALUI PENGEMBANGAN TANAMAN Azolla mirophylla DI KABUPATEN BREBES - Supartoto; Roesdiyanto; Dalhar Shodiq (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2019)
The purpose of these activities were to socialized cultural technique and the use of A.microphylla as green meal alternative of layer duck, to develops A. microphylla culture in one of centra duck farm in Brebes, and indentify and make innovation on the potentials of Limbangan Wetan to support the development of village innovation. Methodes used in these activities were extension, demonstration plot, and field assistance through involving student Kuliah Kerja Nyata (the real work of lecture). The result showed that: (1) Duck farmer group Berhias has succeded made 14 units azolla pond and one introduced pond nila fish, (2) The duck farmer group has also implemented the use of azolla as green meal alternative for duck layer and in duck nursery, (3) The duck farmer group responded to the use of azolla as green meal alternative both on layer duck and duck nursery was very good, those were azolla increased duck appetite, increased egg production, stabilized egg production on high level (>70%),increased egg shell quality of old duck, from light green blue to heavy green blue, and increased the health and decreased mortality of baby duck. The positive respond of duck farmer group showed by the increased of number azolla pond made by theirselves. (4) Cultural teqnique of azolla in Limbangan Wetan (the location is close to shore) needed to be modified caused by an extreem local climate and water quality, such as very hot air temperature, high salinity of water, and the exist of pest that usually attack red onion. The solution were put paranet above the pond as a shelter to reduce the pond temperature, temporaly replace the pond water to lower the water salinity, and put stiroform or aluminium foil a long the side of pond to avoid butterfly to put their eggs on the azolla leaf, (5) Student that did KKN have succeded created three food innovation products based on local potential, those were sosis itik, pergedel gulung, Bakso Bandeng and road map of the development of duck farmer group.